A first-principles study of Nb-doped NaAlH4 (001) surface. (March 2019) - Yu, Suye; Li, Shina; Wan, Chubin; Ju, Xin
Abstract: Herein, the structural, electronic and energetic properties of Nb-doped NaAlH4 (001) from the surface to bulk have been studied by first principles calculations. Nb doping introduces charge transfer from Nb atom to Al atoms due to abundant electrons. On one hand, this will reduce the giving effect of electrons from H to Al atoms. On other hand, the original AlH4 groups are distorted by the strong interaction between Nb and Al atoms. These results facilitate the removal of H atoms from the Al atom. The dual effects of Nb doping are also analyzed in different layers. In the top and second layers, the covalent interaction between Nb and Al contributes to the formation of NbAl phase. In deeper layers, the strong interaction between Nb and H atoms reduces the electrons densities around Al, the shortage of electrons favors AlH2 unit attracts its around AlH4 unit to form the Al2 H6 unit. The calculated ab initio molecular dynamics properties indicate that high temperature firstly improves the diffusion of Al atoms from Nb. The NbH2 phases may formed accompanied by the removal of Al atoms. Thus, the catalytic process of Nb in the dehydrogenation of NaAlH4 has been given. Highlights: Nb doping into the NaAlH4 from the (001) surface to bulk is studied. The dual effects of Nb doping in different layers are analyzed. The shortage of electrons favors AlH2 attracts its around AlH4 to form Al2 H6 unit. The NbH formed accompanied by the removal of AlHx unit at high temperature.